AICCRA Senegal field visit programm - Worou, Nadine; Whitbread, Anthony M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This document summarizes the highlights of a field visit by a delegation from the World Bank and AICCRA project partners to Méouane, Senegal, in conjunction with the AICCRA Senegal mid-term review. This document also discusses the activities of the AICCRA project in Senegal, presents the Méouane community, its geography, its agricultural system and practices, its technology parks installed within the framework of AICCRA, etc.